ON NEW MATHEMATICAL METHODS OF CLASSIFICATIONS OF STEEL MOCROSTRUCTURES PICTURES - A. N. Chichko; O. A. Sachek; S. G. Lihouzov (Литьë и металлургия)
Algorithms for classification of the steels microstructures allowing to carry out computer processing of pictures with the purpose of quantitative assessment of the structure characteristics, are offered. It is shown, that using of criteria, which are calculated by spatial position and sizes of pixel spots of different brightness as characteristics of microstructure picture, allows to classify microstructures by level of steel graininess.